MOSAICPLASTY TECHNIQUES IN THE TREATMENT OF OSTEOCHONDRAL INJURIES - Emil Simeonov (Peytchinski Publishing, 2023)
Introduction: Articular cartilage damage is quite a common problem within the general population, especially in the younger and more athletic populations. These defects, if left untreated, would lead to post-traumatic osteoarthritis. Taking into consideration the high frequency and socioeconomic burden of osteoarthritis, the treatment of osteochondral lesions presents a unique challenge for surgeons. Materials/Methods: Several hypotheses were formulated to discover whether mosaicplasty could be used in order to successfully treat osteochondral lesions. Furthermore, open mini and arthroscopic surgery were tested to determine whether they could achieve the same result as mosaicplasty. A sample of 45 patients from the general population volunteered for the study, of whom 13 patients underwent open mosaicplasty, 17 mini-open and 15 patients arthroscopic mosaicplasty. Assessment of the knee articular cartilage reconstruction was done during each visit, utilising Lysholm and the VAS scale. A histological examination was also performed. Results: A significant difference was observed between pre- and post-surgical Lysholm score, as well as between pre- and post-surgical VAS score. Additionally, histological analysis confirmed the success of osteochondral autograft transfer and integration into the recipient's knee. Conclusion: The study demonstrated that several mosaicplasty techniques could be used in articular cartilage reconstruction. Moreover, the histological examination further confirmed the viability of the autograft.